PENGARUH LAJU KALOR TERHADAP EFISIENSI BOILER PADA PABRIK KELAPA SAWIT - Rahimah; Effendi, Zulham; Zakwan (Jurnal Agro Fabrica, 2025)
Several factors that affect boiler efficiency in Palm Oil Mill are saturated pressure, feed water temperature, steam temperature, amount of steam produced, amount of fuel consumption, and calorific value of fuel combustion. The purpose of this study is to obtain the relationship between saturated pressure variations and boiler efficiency, the relationship between feed water temperature variations and boiler efficiency, the relationship between variations in the amount of steam produced and boiler efficiency, and to analyze the calorific value of 75% fiber fuel + 25% shell and Water Tube boiler efficiency. From the analysis results that have been carried out, it was obtained that the relationship between saturated pressure variations and boiler efficiency is not constant, but fluctuates. The relationship between feed water temperature variations and boiler efficiency shows an inconsistent pattern, while the relationship between variations in the amount of steam produced and boiler efficiency is relatively constant and increasing. The high combustion calorific value (HHV) is 21323.584 kJ/kg, and the low combustion calorific value (LHV) is 18083.584 kJ/kg. The highest boiler efficiency value produced is 68% and the lowest boiler efficiency value produced is 49%.